Analysis of the Application of Value Engineering in the Papua Police Headquarters Apartment Building Project - Sinaga, Antas Haulian; Erwin, Erwin (West Science Interdisciplinary Studies, 2025)
This study discusses the application of Value Engineering in the construction project of the Papua Regional Police Flats (Papua Regional Police Flats) located in Koya Koso, Jayapura City. The main objectives are to identify high-cost work items, propose more economical material alternatives without compromising function and quality, and determine potential cost savings. The research follows the five stages of Value Engineering: information, creative, analysis, development, and recommendation. The analysis revealed that floor slabs, columns, and beams were the most cost-intensive components. Through material substitution and technical-economic evaluation, several feasible alternatives were proposed. The total cost savings achieved from implementing these alternatives amounted to IDR 1,054,481,004.59. These findings demonstrate that Value Engineering can significantly improve cost efficiency in construction projects without reducing work quality.